The Impact of Arabic Textbooks on Students’ Motivation and Reading Skills in Higher Education - Nikmah, Khoirin; Himam, Alin Safaraz; Nurkholis, Muhammad Asdi; Adella, Shinta; Wulandari, Retno; Sinaga, Alfin Nurfauzi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to explore the influence of using Arabiyah Bayna Yadayk and Silsilah Ta‘līm al-Lughah al-‘Arabiyyah as instructional media in Arabic language learning at the higher education level, with a specific focus on improving reading skills (maharah qirā’ah). The research employed a descriptive qualitative design. The primary data sources consisted of students enrolled in the Arabic Language Education Program at Universitas Muhammadiyah Purwokerto. Meanwhile, the secondary data sources consisted of two Arabic textbooks, namely Silsilah Ta‘lim al-Lughah al-‘Arabiyyah and Al-‘Arabiyyah Bayna Yadaik. Primary data were collected through a questionnaire. Additionally, classroom observations were conducted to assess students’ engagement, participation, and reading behavior during the learning process. Documentation in the form of students’ reading test results was also collected to support the findings. Data analysis was conducted in several stages. Questionnaire responses were analyzed descriptively and thematically. Then, observation data were analyzed by comparing classroom behavior with students’ reading test results. Furthermore, content analysis was applied to examine the characteristics of both textbooks. The results showed that both textbooks demonstrate a strong correlation with students’ motivation in learning theherabic language. The supportive design, accessible vocabulary, and cultural elements of Arabiyah Bayna Yadayk particularly enhance reading skills and encourage consistent engagement. Meanwhile, Silsilah Ta‘līm al-Lughah al-‘Arabiyyah contributes to vocabulary expansion and sustained reading practice, thereby reinforcing students’ overall linguistic competence and academic confidence.